University faculty members' attitudes towards student centred learning - Wong, Su Luan; Abu Bakar, Kamariah; Mohd Ayub, Ahmad Fauzi; Lope Pihie, Zaidatol Akmaliah (Universiti Putra Malaysia Press, 2016)
The Malaysian National Higher Education Strategic Plan launched in 2011 by the Ministry of Higher Education emphasised the student centred learning (SCL) approach for all institutions of higher education. In SCL, the focus of instruction is transferred from the teacher to the students who are expected to take greater responsibility for learning. The strategic plan also calls for a strengthening of higher education faculty members’ capacity in implementing SCL in the learning environment. Based on the aforesaid reasons, it is important for lecturers to be competent in implementing SCL. At the same time, it is also important to ensure that they possess positive attitudes towards SCL. Affective characteristics should not be overlooked as there is evidence to suggest the link between attitude and behaviour. This study explores faculty members’ attitudes towards SCL at a leading research university in Malaysia. The study also examined if gender and academic seniority had an impact on the SCL attitudes of lecturers. Descriptive results revealed that faculty members possessed positive attitudes towards SCL. Gender made a difference in attitudes towards SCL, with female faculty members favouring the SCL approach more than their male counterparts. Academic seniority, however, did not have a bearing on preference towards SCL.